Multimodal meta-analysis of structural and functional brain changes in first episode psychosis and the effects of antipsychotic medication - Radua, Joaquim; Meyer-Lindenberg, Andreas (Neuroscience & biobehavioral reviews, 2012)
Structure and function in the human brain are closely related. At the onset of psychosis, brain imaging studies have identified robust changes in brain function and structure, but no data are available relating these two domains. After systematic literature searches, we included all available studies reporting whole-brain structural or cognitive functional imaging findings in first-episode (FEP) subjects in multimodal Signed Differential Mapping (SDM). Forty-three studies met the inclusion criteria. The structural database comprised 965 FEP subjects matched with 1040 controls whilst the functional cohort included 362 FEP subjects matched with 403 controls. The analysis identified conjoint structural and functional differences in the insula/superior temporal gyrus and the medial frontal/anterior cingulate cortex bilaterally. In these regions, large and robust decreases in grey matter volume were found with either reduced or enhanced activation. Meta-regression analyses indicated that grey matter volume in the anterior cingulate and left insular clusters was influenced by exposure to antipsychotics: patients receiving medication were more likely to show structural abnormalities in these regions.